Do Yoga Be Sustainable: Examination of sustainable consumer behaviour of yoga practitioner - Yüce, Arif (2021)
One of the most critical conditions for individuals to develop and adapt the sustainable consumption understanding is to create sustainable consumer behaviors. Therefore, it is considered important that the individuals become conscious and act with sustainable consumption behaviors. At this point, examining the current circumstances for the relationship between Yoga and sustainable consumer behaviors and knowing the effects of Yoga on sustainable consumption behavior is one of the significant matters that must be assessed within the scope of sustainable consumer behavior and the context of sports and health services sector. Accordingly, the aim of present study was to examine and compare the sustainable consumption behaviors of yoga practitioners environmentally, economically, and socially. The sample of the study was consist of 307 yoga practitioners. To determine sustainable consumer behavior of yoga practitioners, the “Sustainable Sports Consumer Behavior Scale” was used. Sustainable consumer behavior of yoga practitioners was examined through descriptive analysis. In comparisons, t-test and one-way analysis of variance (ANOVA) were used. Also, Bivariate correlation analyses were used to examine the relationship with some variables. As a result of the research, it was found that yoga practitioners have a high level of sustainable consumption behaviors. Besides, it has been determined that the sustainable behaviors of yoga practitioners do not differ based on variables such as education and age but differ based on yoga experience. In this regard, it has been concluded that, as the yoga experience of individuals increases, their tendency to behave as sustainable consume also increases.